2015
DOI: 10.1186/s13014-015-0407-7
|View full text |Cite
|
Sign up to set email alerts
|

Textural features in pre-treatment [F18]-FDG-PET/CT are correlated with risk of local recurrence and disease-specific survival in early stage NSCLC patients receiving primary stereotactic radiation therapy

Abstract: BackgroundTextural features in FDG-PET have been shown to provide prognostic information in a variety of tumor entities. Here we evaluate their predictive value for recurrence and prognosis in NSCLC patients receiving primary stereotactic radiation therapy (SBRT).Methods45 patients with early stage NSCLC (T1 or T2 tumor, no lymph node or distant metastases) were included in this retrospective study and followed over a median of 21.4 months (range 3.1–71.1). All patients were considered non-operable due to conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 32 publications
6
94
2
1
Order By: Relevance
“…1). These results are contrary to findings in [ 18 F]FDG PET studies investigating TF in pancreatic ductal carcinoma or non-small cell lung cancer (low entropy associated with longer OS) [41,42]. Understandably, results from […”
Section: Discussioncontrasting
confidence: 90%
“…1). These results are contrary to findings in [ 18 F]FDG PET studies investigating TF in pancreatic ductal carcinoma or non-small cell lung cancer (low entropy associated with longer OS) [41,42]. Understandably, results from […”
Section: Discussioncontrasting
confidence: 90%
“…Given that conventional indices, such as standard uptake value (SUV), maximum or metabolic tumor volume (MTV) are insufficient to characterize malignancies [268], several groups have started to investigate the feasibility of in vivo tumor characterization in the context of textural evaluation [269]. As a result of this initiative, first reports have appeared that point at promising results of a quantitative assessment of tumor heterogeneity in light of therapy response prediction [270,271], disease-specific survival [272] as well as prognostic stratification [273]. Meanwhile, challenges using textural features remain, since such calculations are highly sensitive to acquisition, reconstruction and sample size variations [274][275][276].…”
Section: In Vivo Disease Characterizationmentioning
confidence: 99%
“…Pyka et al recently reported on the significance of textural PET features in 45 patients who were treated with stereotactic body radiotherapy for early-stage NSCLC (26). Seven local recurrences occurred among the 30 patients with T2 (>3 cm) tumors, and no local recurrences were seen in patients with smaller tumors.…”
Section: Discussionmentioning
confidence: 99%